Bilateral carpal tunnel syndrome due to gouty tophi: conservative and surgical treatment in different hands of the same patient. Issue 2 (March 2015) - Onuma, Kenji; Fujimaki, Hisako; Kenmoku, Tomonori; Sukegawa, Koji; Takano, Shotaro; Uchida, Kentaro; Takahira, Naonobu; Takaso, Masashi
Abstract Gouty tophi are an uncommon cause of carpal tunnel syndrome. We describe a case of bilateral carpal tunnel syndrome due to gouty tophi. Gouty tophi in the right wrist developed slowly, but developed acutely in flexor tendons in the left wrist. Symptoms were numbness and finger movement dysfunction in both hands. The right hand was treated surgically, while the left hand was treated by medication. Both hands improved under a well-controlled serum uremic acid level.